TRABALHO DOCENTE, ENSINO REMOTO EMERGENCIAL E POLÍTICAS EDUCACIONAIS NO MUNICÍPIO DE TRÊS LAGOAS/MS - Marize Aparecida Leite Siqueira Silva (2022)
Through a case study, with a qualitative approach, we sought if understand the importance of information and communication technologies (ICT) in the school environment and how they affected teaching work during the Covid-19 pandemic. The study also aimed to analyze the contribution of educational policies to the integration of technologies in schools and how they influenced teaching activities in the early years of elementary school in the municipality of Três Lagoas/MS, during the Coronavirus pandemic. The development of the research took place in three stages. The first consisted of a survey of national scientific production on the subject of research in indexing databases of scientific works (Scielo.br, Google Scholar, CAPES Theses and Dissertations Bank, and Digital Library of Theses and Dissertations), seeking to analyze trends in productions on the subject of this research. In the documentary part of the research, it was carried out a survey and analysis of the Laws and Decrees of the Federal Government, the State of Mato Grosso do Sul and the Municipality of Três Lagoas/MS regarding the regulations for the operation of public and private educational units. during the pandemic period. The second stage of the research consisted of conducting focus groups, having as participants’ teachers and pedagogical coordinators who work in the early years of elementary school in the municipal education network in the municipality of Três Lagoas/MS. In the third and final stage, the information collected in the field was organized, transcribed, separated by segments, coded and finally analyzed by categories. The results pointed to the need for educational policies aimed at the development of ICT in schools, through adequate infrastructure and continuing education for teachers. They also demonstrated the difficulties that teachers faced during the pandemic, from the preparation and development of remote classes to the attempt of an innocuous partnership with parents and/or guardians of students for home school support, considering the exponential increase in workload and costs absorbed by the teachers themselves. Finally, there was great uncertainty about the peculiar moment experienced by everyone during the pandemic and the respondents were unanimous in saying that schools, teachers and students must be prepared for the use of ICT in education, and they understand that governments need to invest every increasingly in the technological infrastructure and in the continuing education of teachers.